If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(s + 4) = 10 Reorder the terms: 2(4 + s) = 10 (4 * 2 + s * 2) = 10 (8 + 2s) = 10 Solving 8 + 2s = 10 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 2s = 10 + -8 Combine like terms: 8 + -8 = 0 0 + 2s = 10 + -8 2s = 10 + -8 Combine like terms: 10 + -8 = 2 2s = 2 Divide each side by '2'. s = 1 Simplifying s = 1
| x*13-4.5=0 | | -2(x+5)=-4(x-5) | | 2x-4=4x+12 | | 6y-3y+5y=-4-6 | | 8(6x-3)=120 | | 2(1-7x)=114 | | -7(1+2n)=-119 | | 4x^2-10x+5=x-3 | | 6(x+4)-8=24-6x-8+12x | | 6(5k+2)=252 | | 3(x-6)=x+10 | | 3x^2+29x-12= | | 2(7x-4)=2(11+x) | | 0.6x-0.5(11-3x)=-0.8(x-4) | | 12=3m-21 | | x-401.99=149.80 | | 3x=-5y-12 | | -13=2-7b-8 | | 2y-5=5t+4 | | -48-4x=-7x+21 | | -11=1+4k+8k | | 0.10(s+200.00)=55.00 | | -8r+5=29 | | -6m+2m=20 | | 0.10(s+200.00)=100.00 | | -b+2b=3 | | -7+2b+2=-1 | | 15x+1=12x+3 | | 4n-9=2n+10 | | 3w-8=-26 | | 2(n+2)=8-n | | 7p+8p=15 |